Contextualizing HIV testing experiences within the HIV prevention cascade: qualitative insights from refugee youth in Bidi Bidi refugee settlement, Uganda - Logie, Carmen Helen; Okumu, Moses; Loutet, Miranda; Coelho, Madelaine; McAlpine, Alyssa; MacKenzie, Frannie; Lukone, Simon Odong; Kisubi, Nelson; Kalungi, Hakim; Lukone, Okello Jimmy; Kyambadde, Peter (BMC public health, 2024)
Background There remain key knowledge gaps regarding HIV testing needs and priorities among refugee youth in low and middle-income country (LMIC) humanitarian settings. The HIV prevention cascade framework focuses on three domains (motivation, access, effective use) central to prevention uptake, yet is understudied in relationship to HIV testing, particularly among refugee youth. Uganda is an exemplar context to explore refugee youth HIV testing needs and priorities as it hosts 1.5 million refugees and is Africa’s largest refugee hosting nation. In this study, we explored perceptions and experiences regarding HIV testing among refugee youth living in Bidi Bidi refugee settlement, Uganda. Methods We conducted a community-based research study in Bidi Bidi Refugee Settlement, one of the world’s largest refugee settlements with over 195,000 residents. This qualitative study involved four focus groups (2 with young women, 2 with young men) with refugee youth aged 16–24 living in Bidi Bidi refugee settlement. We applied thematic analysis informed by the HIV prevention cascade to understand domains of motivation, access, and effective use that emerged as salient for HIV testing engagement. Results Participants ( n = 40; mean age: 20 years, standard deviation: 2.2) included refugee young women ( n = 20) and young men ( n = 20), of whom 88% had a lifetime HIV test and 58% had ever heard of HIV self-testing. Participant discussions described HIV testing motivation was influenced by dimensions of: HIV treatment and testing knowledge; risk perception; positive and negative consequences of use; and social norms regarding gender and age. Access to HIV testing was shaped by: limited availability; distance and language barriers; confidentiality concerns; and affordability. Effective use of and engagement with HIV testing was related to HIV serostatus knowledge self-efficacy and in/equitable partner dynamics. Conclusions Complex, multi-level factors shape motivation for, access to, and effective use of HIV testing among refugee youth in Bidi Bidi. Findings align with the HIV prevention cascade framework that helps to identify gaps to inform intervention development with youth in humanitarian settings. HIV testing approaches tailored for refugee youth in contexts such as Bidi Bidi can foster HIV prevention and treatment literacy, gender equity, gender-based violence prevention, and intersectional stigma reduction.